Prvi rezultati raziskav kamnine v treh lunanskih kamnitih gozdovih (Yunnan, Kitajska) - Knez, Martin (Acta carsologica, 1997)
In some areas of Lunan county the composition of the rock is very monotonous but in some places the geological profiles show alternation of different types of limestones and dolomites. This results in selective corrosion and erosion of carbonates and therefore affects the appearance of separated stone pillars, of the bigger rock blocks and of the landscape relief.
Keywords: erozija; geomorfologija; geomorphology; karbonatne kamnine; Kitajska; korozija; kras (geologija); Yunnan